Noninvasive Management of Fractured Indwelling Tunneled Pleural Catheter Valve. (13th August 2022) - Shahid, Azib; Singh, Harpreet; Espina, Toni-Denise; Abdalla, Mohammad; Ghori, Uzair; Benn, Bryan S.
Abstract : Tunneled indwelling pleural catheters (IPCs) are frequently used to palliate symptomatic dyspnea due to recurrent pleural effusions. The drainage valve of IPCs is an important component of the catheter as fracture of the valve leads to malfunctioning of the IPCs. Replacement of the catheter includes risks such as pain, infection, pneumothorax, and procedure cost. We report two cases of malfunctioning tunneled IPC drainage valves repaired by our noninvasive method and discuss the need for a repair kit and a standardized approach to this repair in case of nonavailability of repair kits.